Effects of Different Doses of Bone Morphogenetic Protein 4 on Viability and Proliferation Rates of Mouse Embryonic Stem Cells - Zohreh Makoolati (Cell Journal, 2009)
Objective: In this study, we examined the effect of different doses of bone morphogeneticprotein 4 (BMP4) on CCE mouse embryonic stem cells (ESCs) viability andproliferation rates in order to improve the outcome of induction processes and make asystem with highest viability and proliferation rates for further studies on BMP4 roles inmultiple developmental stages.Materials and Methods: Expression of Oct-4 was studied and confirmed in this cellline immunocytochemically. Also, in order to evaluate the proliferation and viabilityrates in BMP4-treated cells, ESCs were cultured in Dulbecco's Modified Eagle Medium(DMEM) containing different doses of BMP4 (0, 0.01, 0.1, 1, 5, 25, 50 and 100ng/ml).The mean number of whole cells and living cells were considered as proliferation andsurvival rates respectively. Data analysis was done with ANOVA test.Results: The results showed that there were significant differences between the meanpercent of viability between 1ng/ml and 0 ng/ml (control) and 50 and 100 ng/ml BMP4(p≤0.01), as well as between 5 ng/ml and 0, 0.01, 0.1, 25, 50 and 100 ng/ml BMP4(p≤ 0.02). Also, significant differences were observed in proliferation rates between 5ng/ml and 0, 0.01, 0.1, 1, 25 and 100 ng/ml BMP4 (p≤0.01), 25 ng/ml and 0.01, 1 and5 ng/ml BMP4 (p≤0.01), as well as between 50 ng/ml and 0.01 and 0.1 ng/ml BMP4(p≤0.001).Conclusion: The results suggest that addition of 5ng/ml BMP4 had the best effects onthe proliferation and viability rates of CCE mouse ESCs.